The Instruction of Balance and Its Measurement in Professional Physical Therapy Education Programs. Issue 4 (December 2018) - Oates, Alison R.; Santoro, Regan; Arnold, Catherine; Sibley, Kathryn M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Physical therapists (PTs) have an important role in identifying and treating individuals with balance impairments to help modify fall risk; however, gaps in comprehensive assessment of balance among practicing PTs have been consistently identified. As academic preparation influences clinical practice, identifying the balance measurement tools included in entry-level training for PTs is important. In particular, exploring their underlying content in relationship to recognized components of balance described in the Systems Framework for Postural Control can highlight strengths and may identify opportunities to advance training and future practice. The objective of this study was to examine how balance and its measurement are included in entry-level physical therapy education programs. Methods: Faculty from 110 physical therapy programs in Canada and the United States were surveyed on the inclusion of balance components and validated balance measures using an online survey. Results: Descriptive analysis of 95 completed responses illustrated that instructors reported including detailed instruction and practical experience for most balance components. Almost all (26/27) measures included in the survey were included in course content with practical experience by at least one participant. Years of instructing had minimal effect on how the components and/or measures were included in course content. The measures reported to be included with practical experience most often do not assess all components of balance. Discussion and Conclusions: Overall, instructors in participating physical therapy education programs reported providing detailed and practical instruction of commonly used balance measures and multiple components of balance. There is opportunity to enhance instruction by incorporating currently available measures that assess most and/or all balance components to ensure newly educated PTs are equipped to comprehensively assess and treat balance to improve fall prevention efforts.